Pemenuhan Gizi Anak Di Lembaga Pembinaan Khusus Anak Kelas II Batam : Kajian Terhadap Pengaturan Konsumsi Susu Dalam Kerangka Peraturan Menteri Hukum Dan HAM Nomor 40 Tahun 2017 - Jefriandi Jefriandi; Muhammad Hasan Sebyar (Jembatan Hukum : Kajian ilmu Hukum, Sosial dan Administrasi Negara, 2024)
The problem in this research is that there is still a lack of nutritional intake such as milk provided by LPKA Class II Batam, this is due to a lack of budget. The aim of this research is to find out how children's food is implemented in fulfilling children's nutrition and providing milk to children at LPKA Class II Batam. The type of research approach used is empirical juridical, where research uses legal aspects (observation with reality in the field). Based on the results of this research, it can be concluded that the implementation of providing milk for assisted children is still not going well, namely that assisted children are only given milk according to their needs and these children do not even receive milk regularly. This is because the budget given to LPKA Class II Batam is inadequate to provide milk to the children assisted regularly and comprehensively. To comply with the Minister of Law and Human Rights Regulation, the LPKA Class II Batam has provided food to children in accordance with Minister of Law and Human Rights Regulation Number 40 of 2017 concerning Guidelines for Food Administration. For Prisoners, Children and Prisoners. Assisted children are given food 3 times a day and the food provided contains good nutrition